Jump landing characteristics predict lower extremity injuries in indoor team sports - van der Does, H. T. D.; Brink, M. S.; Benjaminse, A.; Visscher, C.; Lemmink, K. A. P. M. (International Journal of Sports Medicine, 2016)
The aim of this study is to investigate the predictive value of landing stability and technique to gain insight into risk factors for ankle and knee injuries in indoor team sport players. Seventy-five male and female basketball, volleyball or korfball players were screened by measuring landing stability after a single-leg jump landing and landing technique during a repeated counter movement jump by detailed 3-dimensional kinematics and kinetics. During the season 11 acute ankle injuries were reported along with 6 acute and 7 overuse knee injuries by the teams` physical therapist. Logistic regression analysis showed less landing stability in the forward and diagonal jump direction (OR 1.01-1.10, p=0.05) in players who sustained an acute ankle injury. Furthermore landing technique with a greater ankle dorsiflexion moment increased the risk for acute ankle injury (OR 2.16, p=0.05). A smaller knee flexion moment and greater vertical ground reaction force increased the risk of an overuse knee injury (OR 0.29 and 1.13 respectively, p=0.05). Less one-legged landing stability and suboptimal landing technique were shown in players sustaining an acute ankle and overuse knee injury compared to healthy players. Determining both landing stability and technique may further guide injury prevention programs.